European market integration and the determinants of firm localization: The case of Poland - Agnieszka Gehringer; Astrid Krenz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
The paper analyses empirically the determinants of firms localization in Poland. We use regional data of the sixteen Polish administrative regions over the period 2003 to 2010 to examine which role agglomeration forces and other factors played in explaining the choice to operate in a certain location. Our results suggest that agglomeration economies stemming in particular from the R&D sector, as well as human capital and the infrastructure positively influence the regional localization of firms. Polands accession to the European Union had a positive impact for the location decision of new firms in the Polish economy.
Keywords: F14; F15; F23; R11; R12; 330; localization; agglomeration economies; knowledge externalities; Polish regions; European integration